“Nearest Zero-point” Algorithm for Cooperative Robotic Search Missions - Vahid Aryai; Mahsa Kharazi; Farid Ariai (IAES International Journal of Robotics and Automation (IJRA), 2017)
Four path planning and data exchange algorithms for cooperative search and coverage robotic missions are proposed and modified. The introduced methods are simulated using C++ programming environment and the results are discussed in detail for environments with static obstacles. It has been shown that using the “nearest zero-point” algorithm can greatly optimize the mission duration and also overlapping of the search trajectories. Finally, the results are compared with several existing algorithms.